BEBERAPA CATATAN TENTANG PENGAJARAN AKUNTANSI PENGANTAR - Al Haryono Yusuf (Journal of Indonesian Economy and Business (JIEB), 1998)
This paper presents a few footnotes pertaining to instructors' teaching approaches to introductory accounting classes, most notably Akuntansi Pengantar I. Unquestionably, since this course is notably the very first accounting course underlying accounting, instructors' approach to teaching this introductory accounting class plays a vita! role in helping beginners to sufficiently comprehend accounting in a solid perspective. A sound, logical approach will provide frameworks for a better integrity and continuity among the subsequent accounting courses. However, the majority of this paper merely addresses several hints concerning with instructors' approaches to teaching the following pivotal introductory accounting topics, basic accounting equation, debiting and crediting rules, adjusting entries, worksheet, reversing entries, closing entries, balance sheet after closing entries, and eventually cost and non cost of goods sold approaches to accouniingfor merchandising enterprises.